Targeting GSTP1-dependent ferroptosis in lung cancer radiotherapy: Existing evidence and future directions - Tan, Xin; Huang, Xiang; Niu, Baolong; Guo, Xingdong; Lei, Xiao; Qu, Baolin (Frontiers in Molecular Biosciences, 2022)
Radiotherapy is applied in about 70% patients with tumors, yet radioresistance of tumor cells remains a challenge that limits the efficacy of radiotherapy. Ferroptosis, an iron-dependent lipid peroxidation regulated cell death, is involved in the development of a variety of tumors. Interestingly, there is evidence that ferroptosis inducers in tumor treatment can significantly improve radiotherapy sensitivity. In addition, related studies show that Glutathione S-transferase P1 (GSTP1) is closely related to the development of ferroptosis. The potential mechanism of targeting GSTP1 to inhibit tumor cells from evading ferroptosis leading to radioresistance has been proposed in this review, which implies that GSTP1 may play a key role in radiosensitization of lung cancer via ferroptosis pathway.